An analysis on the relationship between emotional intelligence and conflict management strategy : evidence from Turkey - Yücel, Gizem (My University, 2019)
Çatışma hayatın her anında insanların iletişim ve etkileşimde bulunduğu her sosyal ortamda ortaya çıkması kaçınılmaz bir olgudur. Meydana gelen çatışmalar, kişilerin durumlara göre seçtiği beş farklı strateji (stil) ile karşılanabilir. Literatüre bu stratejiler Problem Çözme,Uyma, Zorlama, Uzlaşma ve Kaçınma olarak tanımlanmıştır. Bu araştırmada kendi ve karşının duygularını anlayıp yönetmek olarak tanımlanan duygusal zekanın çatışma yönetim stratejileri üzerinde nasıl bir etkisi olduğu araştırılmıştır. Bunun için hazırlanan ve rastgele gönderilen anket çalışmasından 304 kişiden gelen dönüşlere göre duygusal zeka ve çatışma yönetimi stratejileri arasında pozitif bir ilişki olduğu belirlenmiştir

Conflict is an inevitable phenomenon that occurs in every social environment where people communicate and interact. From the literature, conflicts may be manage with five different strategies, depending on the circumstances. These strategies are defined as Integrating Style , Accommodating Style, Competing Style, Avoiding Style and Compromising Style. In this study, the relationship has been investigated relationship conflict management strategies and emotional intelligence, which is defined as understanding and managing the feelings of self and others’. It was determined that there is a positive relationship between emotional intelligence and conflict management strategies according to the returns from 304 participant who were randomly sent survey.
Keywords: Business; Çatışma Yönetimi Stratejileri; Duygusal Zeka Conflict Management Strategy; Emotional Intelligence; İşletme; Management; Yönetim